Phytochemical study of alkaloids of Xylopia Ferruginea / Norwahida Zamani - Zamani, Norwahida (Faculty of Applied Sciences, 2009)
139 fractions of the ethyl acetate crude extract of Xylopia ferruginea were analyzed for their alkaloidal content. The 139 crude fractions were monitored using conventional method of thin layer chromatography (TLC). Two fractions (fractions 28 and 29) gave the best separation and were found to have the same profile based on their spots' Rf value. Fractions 28 and 29 separated into three spots each and the three spots having same Rf value of 0.38, 0.49 and 0.58 respectively. Fractions 28 and 29 also give positive result of Dragendorff's test by forming red-orange spot after spraying with the reagent. Both fractions were combined and purified using preparative thin layer chromatography (preparative TLC) and then analyzed using IH NMR. The deduced alkaloid found to be a new substituted oxoaporphine alkaloid which employ similar splitting pattern with liriodenine. The deduced alkaloid is possibly a dihydroxy-methoxy-substituted liriodenine.